Revealing the role of oxygen vacancies on the phase transition of VO2 film from the optical-constant measurements. Issue 34 (24th May 2018) - Fan, Lele; Wang, Xiangqi; Wang, Feng; Zhang, Qinfang; Zhu, Lei; Meng, Qiangqiang; Wang, Baolin; Zhang, Zengming; Zou, Chongwen
Abstract : Optical conductivity spectroscopy was performed to reveal the role of oxygen vacancies during VO2 metal–insulator transition. Abstract : Vanadium dioxide (VO2 ) material shows a distinct metal–insulator transition (MIT) at the critical temperature of ∼340 K. Similar to other correlated oxides, the MIT properties of VO2 is always sensitive to those crystal defects such as oxygen vacancies. In this study, we investigated the oxygen vacancies related phase transition behavior of VO2 crystal film and systematically examined the effect of oxygen vacancies from the optical constant measurements. The results indicated that the oxygen vacancies changed not only the electron occupancy on V 3d–O 2p hybrid-orbitals, but also the electron–electron correlation energy and the related band gap, which modulated the MIT behavior and decreased the critical temperature resultantly. Our work not only provided a facile way to modulate the MIT behavior of VO2 crystal film, but also revealed the effects of the oxygen vacancies on the electronic inter-band transitions as well as the electronic correlations in driving this MIT process.